2020
DOI: 10.1177/1938965520968065
|View full text |Cite
|
Sign up to set email alerts
|

The Emancipatory Approach in Hospitality Research on Employees With Disabilities: An Auto-Ethnographic Research Note

Abstract: The emancipatory approach in disability research takes the political position of promoting the voices of people with disabilities to make possible transformative changes to their lives. Based on auto-ethnographic research notes made while applying the emancipatory approach to qualitative research conducted with employees with disabilities in the Vietnamese hospitality industry, this article suggests guidelines that include four steps: preparing/planning, recruiting, conducting interviews, and confirming the da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 52 publications
0
11
0
4
Order By: Relevance
“…The primary investigator grew up in Vietnam and has had extensive hospitality industry work experience, so was thus familiar with the local culture and the development of the industry, and had good networks in the research context; this was helpful for interpreting the participants’ responses and “ensur [ing] first-hand knowledge” (Paraskevaidis and Andriotis, 2017: 30) was obtained. Furthermore, this researcher was acutely aware of the cultural challenges facing Vietnamese participating in this research (see Doan et al, 2020). Therefore, the primary investigator employed various communication strategies (e.g., using standardized language, asking and listening sequences, expressing gratitude, etc.)…”
Section: Methodology and Methodsmentioning
confidence: 99%
“…The primary investigator grew up in Vietnam and has had extensive hospitality industry work experience, so was thus familiar with the local culture and the development of the industry, and had good networks in the research context; this was helpful for interpreting the participants’ responses and “ensur [ing] first-hand knowledge” (Paraskevaidis and Andriotis, 2017: 30) was obtained. Furthermore, this researcher was acutely aware of the cultural challenges facing Vietnamese participating in this research (see Doan et al, 2020). Therefore, the primary investigator employed various communication strategies (e.g., using standardized language, asking and listening sequences, expressing gratitude, etc.)…”
Section: Methodology and Methodsmentioning
confidence: 99%
“…In the tourism and hospitality sector, PWD are increasingly appearing in various job roles and levels of responsibility (Meacham et al, 2019;Mooney & Baum, 2019), but experts still speak of "untapped potential" for the employment of PWD (Doan et al, 2021). Despite the entry discrimination, the more significant presence of PWD in the workforce could bring the sector multiple and complex benefits in human resource management, marketing, innovation or inclusive organisational culture (Kalargyrou et al, 2018).…”
Section: Employment Of Pwd and The Hospitality Sectormentioning
confidence: 99%
“…In relation to employment, this sector also identifies the general labour market barriers that have already been discussed: a general lack of information on the part of employers and employees, communication difficulties, stereotypes, a lack of employment support systems, competency gaps (also) resulting from the training system, and the perceived or real costs of accessibility (Houtenville & Kalargyrou, 2012). However, Doan et al, (2021) also identify sector-specific factors such as stigma associated with disability and possible consumer perceptions related to service quality (Doan et al 2021). Gröschl (2007) suggests that the tourism and hospitality segment basically seek young and attractive workers who are able to multitask, are flexible, able to work long hours and in any position.…”
Section: Employment Of Pwd and The Hospitality Sectormentioning
confidence: 99%
See 1 more Smart Citation
“…In the second implementation-based qualitative paper, Doan et al (2021) provide a research note on auto-ethnographic research in the specific context of hospitality employees with disabilities. The authors report that of 1,091 articles identified using the search terms “disability” and “disabled,” “handicapped,” and “impairment,” only three actually include employees with disabilities as research participants.…”
Section: Special Issue Articlesmentioning
confidence: 99%